Peak expiratory flow rate monitoring can predict asthma exacerbation better as compared to monitoring by symptoms, prospective cohort study - Gupta, Sarika; Shabnam,; Verma, Ajay K. (International Journal of Contemporary Pediatrics, 2024)
Background: Global initiative for asthma (GINA) guidelines suggest to use peak expiratory flow rate (PEFR) monitoring to assess response to treatment, to identify triggers for exacerbation and to have a baseline value for action plan (especially for the poor perceivers). In comparison to adults, there are less evidence in support of the routine use of PEFR recording for the diagnosis and monitoring level of control of asthma in children. This study was conducted with objective to assess the effect of PEFR monitoring on numbers of exacerbations in comparison to monitoring by symptoms in asthma. Methods: This was a prospective cohort study done for a in department of pediatrics and respiratory medicine, of a tertiary care hospital, North India. Prior to recruitment ethical approval and informed consent/assent was taken. Study subjects were children with partial and uncontrolled asthma aged 5-12 years of age. Patients were divided into two groups on their first visit by using random allocation number. In group “A” monitoring was done with symptoms only, while in group “B” monitoring was done by symptoms and PEFR. Number of exacerbations during study period was noted. At baseline and follow up, CACT score was calculated. Spirometry was done at the end of 3 months. Results: Group B had statistically significant lesser exacerbation during study period as compared to group A (OR=0.23; 95% CI=0.06-0.81; p=0.020). Conclusions: PEFR based monitoring can be used as a potential tool for aborting or decreasing the severity of episodes of exacerbations of asthma especially in resource limited areas.